Rootletin, a novel coiled-coil protein, is a structural component of the ciliary rootlet - Yang, Jun (The Rockefeller University Press, 2002)
The ciliary rootlet, first recognized over a century ago, is a prominent structure originating from the basal body at the proximal end of a cilium. Despite being the largest cytoskeleton, its structural composition has remained unknown. Here, we report a novel 220-kD protein, designated rootletin, found in the rootlets of ciliated cells. Recombinant rootletin forms detergent-insoluble filaments radiating from the centrioles and resembling rootlets found in vivo. An mAb widely used as a marker for vertebrate rootlets recognizes an epitope in rootletin. Rootletin has a globular head domain and a tail domain consisting of extended coiled-coil structures. Rootletin forms parallel in register homodimers and elongated higher order polymers mediated by the tail domain alone. The head domain may be required for targeting to the basal body and binding to a kinesin light chain. In retinal photoreceptors where rootlets appear particularly robust, rootlets extend from the basal bodies to the synaptic terminals and anchor ER membranes along their length. Our data indicate that rootlets are composed of homopolymeric rootletin protofilaments bundled into variably shaped thick filaments. Thus, rootletin is the long-sought structural component of the ciliary rootlet.